The Impact of Institutional Pluralism on Governmental Reforms in the Public Sector: Choice, Monitoring and Licenses in Swedish Schools - Blomgren, Maria; Waks, Caroline (Scandinavian Journal of Public Administration, 2017)
The aim of this article is to investigate the influence of institutional pluralism on the expansion of reforms in the public sector. The paper seeks to contribute to the Scandina- vian institutionalism perspective where previous analyses of reforms have often used a case-study methodology and focussed on one, or a few, reforms attributable to the same institution. The focus of this article is to describe and analyse the reform history in order to capture the dynamics between reforms attributable to different institutions. An analysis of the reforms of the Swedish school system between 1990 and 2013 is conducted reve- aling that more than 70 reforms were implemented during the period. The reforms were based on different institutions such as ‘the market’, ‘the state/bureaucracy’ and ‘the pro- fession’. This plurality of reforms casts new light on the expansion of reforms as it sug- gests that the dynamics are not only characterised by completions as has previously been shown, but also by counterbalances in relation to the institutions involved.